Three-point bending response of laser-welded sandwich structure with varying number of core and span length - N. K., Romli; Xiaoxia, Jiang; S. M., Sofie; M. R. M., Rejab (IOP Publishing, 2020)
Laser welding offered multiple benefits for production of all-metal and hybrid-metal sandwich structure. Deep penetration of laser welding required high energy intensity and low heat input. Normally, steel sandwich structure dominated failure features. The objective of this study to investigate the failure of laser-welded sandwich structure under three-point bending test. Bending deformation of the sandwich structure was studied with numerical modelling. The sandwich panels were studied on different number of core and span length of experimental. The role of core number to determine overall deformation and local failure response of the sandwich panel were studied. Face and web plates were assembled perpendicularly via fibre laser welding. The sandwich panel modelled by using Abaqus to predict response of the sandwich panel under bending loading. The aim of this study to compare response of laser-welded sandwich panel from experimental work and numerical modelling. Different span length and core number affected cell wall buckling in corrugated core system. The comparison result showed good agreement with experimental measurements. Percentage error between experimental and FE analysis was 25.60%.